One Gene, Many Facets: Multiple Immune Pathway Dysregulation in SOCS1 Haploinsufficiency - Körholz, Julia; Gabrielyan, Anastasia; Sowerby, John M.; Boschann, Felix; Chen, Lan-Sun; Paul, Diana; Brandt, David; Kleymann, Janina; Kolditz, Martin; Toepfner, Nicole; Knöfler, Ralf; Jacobsen, Eva-Maria; et al. (Frontiers in Immunology, 2021)
Background: Inborn errors of immunity (IEI) present with a large phenotypic spectrum of disease, which can pose diagnostic and therapeutic challenges. Suppressor of cytokine signaling 1 (SOCS1) is a key negative regulator of cytokine signaling, and has recently been associated with a novel IEI. Of patients described to date, it is apparent that SOCS1 haploinsufficiency has a pleiotropic effect in humans. Objective: We sought to investigate whether dysregulation of immune pathways, in addition to STAT1, play a role in the broad clinical manifestations of SOCS1 haploinsufficiency. Methods: We assessed impacts of reduced SOCS1 expression across multiple immune cell pathways utilizing patient cells and CRISPR/Cas9 edited primary human T cells. Results: SOCS1 haploinsufficiency phenotypes straddled across the International Union of Immunological Societies classifications of IEI. We found that reduced SOCS1 expression led to dysregulation of multiple intracellular pathways in immune cells. STAT1 phosphorylation is enhanced, comparably with STAT1 gain-of-function mutations, and STAT3 phosphorylation is similarly reduced with concurrent reduction of Th17 cells. Furthermore, reduced SOCS1 E3 ligase function was associated with increased FAK1 in immune cells, and increased AKT and p70 ribosomal protein S6 kinase phosphorylation. We also found Toll-like receptor responses are increased in SOCS1 haploinsufficiency patients. Conclusions: SOCS1 haploinsufficiency is a pleiotropic monogenic IEI. Dysregulation of multiple immune cell pathways may explain the variable clinical phenotype associated with this new condition. Knowledge of these additional dysregulated immune pathways is important when considering the optimum management for SOCS1 haploinsufficient patients.